RECENT TRENDS IN THE FOOD TRADE SECTOR OF HUNGARY, THE EXAMPLE OF THE LAKE BALATON RESORT AREA - Erzsébet PÉTER; Miklós WEISZ (Journal of Central European Agriculture, 2007)
Following the political transformation of Hungary fundamental changes took place in the trading sector as a consequence of privatization. The influx of active capital considerably influenced the economy and due to its multiplying effects new enterprise management systems, new work comprehension, new service background were established to help the economy participants. Chain formation, trade companies and shopping centres having large floor-space moved into the area with their modern equipments and wide commodity assortment, assisted by foreign capital investment. At the same time national retail trade declined, micro enterprises with few employees lost their survival possibilities in the area. The reply of the food trade sector to the entry of well-capitalized enterprises in the area was that the “chain formation” of smaller retailers became more frequent in the last years in Hungary. This type of transformation made them capable of competing with the big companies.